Impact of early sports specialisation on paediatric ECG. (13th April 2021) - Albiński, Maciej; Saubade, Mathieu; Benaim, Charles; Menafoglio, Andrea; Meyer, Philippe; Capelli, Bruno; Perrin, Tilman; Trachsel, Lukas; Hagemeyer, Daniel; Casagrande, Damien; Wilhelm, Matthias; Pirrello, Tony; et al.
Abstract : Athletes of pediatric age are growing in number. They are subject to a number of risks, among them sudden cardiac death (SCD). This study aimed to characterize the pediatric athlete population in Switzerland, to evaluate electrocardiographic findings based on the International Criteria for electrocardiography (ECG) Interpretation in Athletes, and to analyze the association between demographic data, sport type, and ECG changes. Retrospective, observational study of pediatric athletes (less than 18 years old) including medical history, physical examination, and a 12‐lead resting ECG. The primary focus was on identification of normal, borderline, and abnormal ECG findings. The secondary observation was the relation between ECG and demographic, anthropometric, sport‐related, and clinical data. The 891 athletes (mean 14.8 years, 35% girls) practiced 45 different sports on three different levels, representing all types of static and dynamic composition of the Classification of Sports by Mitchell. There were 75.4% of normal ECG findings, among them most commonly early repolarization, sinus bradycardia, and left ventricular hypertrophy; 4.3% had a borderline finding; 2.1% were abnormal and required further investigations, without SCD‐related diagnosis. While the normal ECG findings were related to sex, age, and endurance sports, no such observation was found for borderline or abnormal criteria. Our results in an entirely pediatric population of athletes demonstrate that sex, age, and type of sports correlate with normal ECG findings. Abnormal ECG findings in pediatric athletes are rare. The International Criteria for ECG Interpretation in Athletes are appropriate for this age group.